WAYS TO IMPROVE ECONOMIC EDUCATION WITH THE HELP OF MODERN TECHNOLOGIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the role and importance of modern multimedia technologies in the process of economic education and upbringing. The effectiveness of multimedia tools in improving the quality of education, simplifying complex economic concepts, increasing students’ interest, and forming practical skills are considered. The article covers the psychological, pedagogical, and economic theoretical foundations of multimedia technologies, as well as their advantages in making the educational process interactive and innovative for students in grades 5-6. It is emphasized that with the help of multimedia tools, it is possible to deepen economic knowledge and develop independent thinking skills. It is shown that in the future, the wider use of multimedia technologies will be of great importance in increasing the effectiveness of education.